Directing adipose‐derived stem cells into keratinocyte‐like cells: impact of medium composition and culture condition. (18th May 2018) - Petry, L.; Kippenberger, S.; Meissner, M.; Kleemann, J.; Kaufmann, R.; Rieger, U.M.; Wellenbrock, S.; Reichenbach, G.; Zöller, N.; Valesky, E.
Abstract: Background: Adipose‐derived stem cells (ASC) are known to transdifferentiate into a wide range of different cell species in vitro including along the epidermal lineage. This property makes them a promising tool for regenerative medicine to restore the epidermal barrier. Objective: This study is dedicated to identify in vitro conditions enabling transdifferentiation to a keratinocyte‐like phenotype. In particular, the impact of different culture conditions (media compositions, 2D, 3D cultures) and extracellular matrix (ECM) molecules was evaluated. Methods: Adipose‐derived stem cells derived from subcutaneous abdominal fat were characterized by stemness‐associated markers and subjected to different media. Epithelial differentiation in 2D cultures was monitored by pan‐cytokeratin expression using flow cytometry and immunocytochemistry. To evaluate the impact of different ECM molecules on epidermal stratification, 3D cultures were produced, lifted to the air–liquid interface (ALI) and examined by histological analysis and quantitative real‐time RT–PCR. Results: We identified a medium composition containing retinoic acid, hydrocortisone, ascorbic acid and BMP‐4 enabling maximum pan‐cytokeratin expression in 2D cultures. Moreover, adhesion to type IV collagen further promotes the pan‐cytokeratin expression. When cultures were lifted to the ALI, significant stratification was observed, particularly in supports coated with type IV collagen or fibronectin. Moreover, epidermal differentiation markers (involucrin, cytokeratin 1 and 14) become induced. Conclusion: Conditions with hampered wound healing such as non‐healing ulcers demand new treatment regimes. The here introduced optimized protocols for transdifferentiation of ASC into keratinocyte‐like cells may help to establish more effective treatment procedures.